Effect of Carbon Fiber Loading in Mechanical Properties and Electrical Conductivity of Polyvinyl Alcohol Based Composites. Issue 1 (July 2015) - Ismadi; Herman Yuwono, Akhmad; Astutiningsih, Sotya; Subyakto; Haryono, Agus; Azuma, Jun‐ichi
Summary Polyvinyl alcohol (PVA) needs to be reinforced with other material to increase its mechanical strength and electrical conductivity to get wider applications. In this research effect of addition of carbon fiber on the mechanical properties and electrical conductivity of PVA based composites was observed. Concentrations of carbon fiber applied were 0, 2, 4 and 6% w/w based on PVA dry weight. PVA film was synthesized by dilute solid PVA in water at temperature of 80 °C for 6 hours with 8% w/w of water, and continued with chilling for 12 h. Carbon fiber was added and stirred by ultra‐turrax for 40 seconds, and the solution was film‐casted. Characterization the composites include morphology analysis (optical microscope and SEM), crystallite size (X‐ray diffraction), mechanical test and electrical conductivity measurement. The result showed that tensile strength increase with increased of carbon fiber added. The optimal value of tensile strength (34.08 MPa) was obtained from 2% w/w of carbon fibers. Addition of 6% w/w of carbon fiber increased electrical conductivity up to 1.33 × 10−3 S/cm, this was significantly enhanced from that net PVA of 2.3 × 10−8 S/cm. Generally, addition of carbon fiber increase tensile strength and electrical conductivity of PVA based composites.